KENYAMANAN TERMAL DAN VISUAL RUANG TERBUKA HIJAU (RTH) DI KOTA PALOPO - Maria Maria; Nardy Noerman Najib; Anugrah Anugrah (Universitas Lambung Mangkurat, 2022)
The quality of the urban environment which continues to decline along with the development of the City means that Green Open Space should not only be considered as a complement to the City. To determine how effective green open space is at determining the comfort of the environment for visitors, the ability of green open space to adjust the microclimate and reduce noise is required. The goal of this study was to find out how different levels of thermal and visual comfort were in different green open spaces in Palopo City. This study took place in Palopo, in the South Sulawesi region. The goal of this study is to look at the level of thermal comfort in Palopo City's five green open spaces, as well as people's impressions of thermal and visual comfort. The results showed that the Thermal and Visual comfort in the five locations of the Green Open Space (RTH) were categorized as uncomfortable because they exceeded the standard comfort criteria, namely temperature >27oC. The results of interviews with visitors' perceptions of Thermal comfort in five green open spaces that were categorized as moderate, visitors assessed that the green open space in these locations was not yet able to provide freshness related to temperature for urban areas due to the lack of vegetated areas. Respondents perceptions of visual comfort in five green open spaces with moderate categories, namely Lapangan Pancasila, Lapangan Gaspa, dan Taman Baca. Meanwhile, the other two green open spaces are categorized as high, namely Lapangan Pancasila dan Taman I Love Palopo. The interpretation of the five green open spaces was categorized as medium & high with the respondents' perceptions both in terms of the architectural form of supporting buildings at each green open space location, existing facilities in green open space, cleanliness in each green open space that was maintained, and tree types that affected the beauty of five green open spaces were considered positively by visitors.The quality of the urban environment which continues to decline along with the development of the City means that Green Open Space should not only be considered as a complement to the City. To determine how effective green open space is at determining the comfort of the environment for visitors, the ability of green open space to adjust the microclimate and reduce noise is required. The goal of this study was to find out how different levels of thermal and visual comfort were in different green open spaces in Palopo City. This study took place in Palopo, in the South Sulawesi region. The goal of this study is to look at the level of thermal comfort in Palopo City's five green open spaces, as well as people's impressions of thermal and visual comfort. The results showed that the Thermal and Visual comfort in the five locations of the Green Open Space (RTH) were categorized as uncomfortable because they exceeded the standard comfort criteria, namely temperature >27oC. The results of interviews with visitors' perceptions of Thermal comfort in five green open spaces that were categorized as moderate, visitors assessed that the green open space in these locations was not yet able to provide freshness related to temperature for urban areas due to the lack of vegetated areas. Respondents perceptions of visual comfort in five green open spaces with moderate categories, namely Lapangan Pancasila, Lapangan Gaspa, dan Taman Baca. Meanwhile, the other two green open spaces are categorized as high, namely Lapangan Pancasila dan Taman I Love Palopo. The interpretation of the five green open spaces was categorized as medium & high with the respondents' perceptions both in terms of the architectural form of supporting buildings at each green open space location, existing facilities in green open space, cleanliness in each green open space that was maintained, and tree types that affected the beauty of five green open spaces were considered positively by visitors.